Short Communications : Microsatellite based association studies for grain mineral content in local winter (Sali) rice of Assam - Pathak, Khanin; Rathi, Sunayana; Verma, H.; Baishya, S.; Sarma, R.N. (The Indian Journal of Genetics and Plant Breeding, 2016)
In present investigation, grains of one hundred indica rice genotypes were analyzed for nine mineral contents namely, phosphorus (P), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), zinc (Zn), iron (Fe), manganese (Mn) and copper (Cu) and genotyped using 112 SSR markers. STRUCTURE analysis identified k=4, indicating at least four distinct groups in a set of 100 rice accessions. Genomewide scanning detected a total of 10 significant markertrait associations (P